THE ANALYSIS OF FACTORS AND CONTEXT THAT INFLUENCE STUDENTS TO USE CODE SWITCHING IN DELIVERING UTTERANCES IN ENGLISH CLASS - Fachrurozy , Ahmad; Puspita, Rani Herning; Sunarti, Sunarti (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Code switching is a phenomenon where people speak using more than one language. The phenomenon happened also in class activity. This research aimed to identify the context and factor that influenced students using code switching. This was qualitative descriptive research. The subject of this research was involved six students of SMK Negeri 4 Samarinda. Students who participated are the 11-grade of acutance class academic year 2021/2022. The data collection in this research was using observation and audio recording. In analyzing the data, the researcher used a modified transcription. Based on the data analysis, this study found that code-switching was occurred in several contexts. The most happened was in the context of question and answer, another context was making comment, and also the opening discussion. The result also found that language ability and the topic of conversation were the factors that influence student to use code switching. In conclusion, the factors code switching was found in this research are language ability and topic of the conversation. Both of that were found in the contexts of question and answer, making comment, and open discussion.